Reassessment of human rights in the context of the Maqāṣid al-Sharī‘ah (High objectives of Islamic law) - Kayadibi, Saim (Turkish Human Rights and Equality İnstitute (TIHEK), 2018)
Given the fact that the high objectives of Islamic law, maqāṣid al-sharī‘ah consists of five values in particular and seven values in general. These are the protection of religion, life, intellect, property, lineage, honour and the state respectively. If one of them falls into danger, the protection of the fundamental rights of the person is also jeopardized. Therefore, simply the protection of these high objectives of Islamic law means also the protection of natural rights of human beings. The practical solution of human rights debates can only be achieved through a sound theoretical foundation. In other words, no concepts and theories that are not well founded cannot find practice in real life. For this reason, it is an inevitable reality that human rights should be evaluated within the context of maqāṣid al-sharī‘ah. The objective of this paper is to highlight the fundamental human rights by giving shed light on the context of the maqāṣid al-sharī‘ah. Content analysis research method is used in this conceptual paper by collecting data from library and secondary resources. This paper, therefore, intended to contribute to the academic research related to the human rights and the concept of maqāṣid al-sharī‘ah by identifying the seven essential values of Islamic law in terms of reassessing human rights in the modern world.